Problems of Foreign Economic Relations Development of Ural Regions with BRICS Countries - Maslennikov, Mikhail Ivanovich (Economy of Regions, 2015)
In the article, the basic vocabulary of BRICS countries, its regional tendencies of business development, and its share taken in the foreign-economic activity are analyzed. Contribution of different foreign trade fields of regions into economic development is revealed. Indicators of development levels of external economic links are reviewed. Alternative options of the foreign trade development, expenses and benefits from its reorientation, and the reason of low indicators of development of foreign trade activity of the Ural regions with BRICS countries are evaluated, and measures for their improvement and development are offered. The mechanism and tools of stimulation of foreign economic relations development of regions with BRICS countries are investigated. The internal and external motives and incentives of expansion of these relations are examined. The factors influencing the regional markets development and revealing multidirectional tendencies in activities of business, government, society for development of foreign economic relations of the Ural regions with BRICS countries, and first of all with Brazil, India, China and the Republic of South Africa are investigated. The export-import features of the foreign trade operations with these countries, and also possible ways and the directions of expansion of the prognostics of foreign economic relations in the conditions of toughening and restriction of similar operations and financial sources from the developed countries, first of all the USA and EU countries are represented. Author examines the reasons and scenario, problems and difficulties for the country and the Ural regions in refocusing of international economic relation from Western Europe to the South-East Asia countries. Real opportunities of participation of regions of the country in the import substitution and development of own resource and production base are analyzed. The research is focused on analysis of international economic relations of the Middle-Ural enterprises with BRICS countries, on identification of causes and effects for enterprises of the old industrial region of reduction of export-import transactions on both developed, and emergent markets in the conditions of toughening and instability of environment in the national and world financial markets.